UPAYA PENINGKATAN KUALITAS GEOMETRIK CITRAUPAYA PENINGKATAN KUALITAS GEOMETRIK CITRA LAPAN-TUBSAT PADA APLIKASI SURVEILEN - Rokhmana, Catur Aries; Judianto, Chusnul Tri (BRIN Publishing, 2011)
Indonesia has developed and operates the LAPAN-TUBSAT micro satellite since 2007 for supporting the surveillance application to observe the earth surface. LAPAN-TUBSAT satellite carried a video camera as an imaging sensor with 5 m ground resolution and 3.5 km swath. Data from this camera still have a weak geometric. This paper will reviews regarding LAPAN-TUBSAT data processing from video recordings as an effort to increase the geometric quality of the LAPAN-TUBSAT image. The correction model rectification of a simple single photograph is used for geometric correction. While the using of super resolution operator for increasing the video image resolution. The correction model rectification of a simple single photograph is used for geometric correction. While the super resolution operator attempted to efforts to increase the resolution of the video image. The experimental results shows geo-reference image with better geometric quality. The evaluation of LAPAN-TUBSAT performance should be carried out In the near future especially for providing Altitude information (Z). This is related to satellite manoeuvre ability to generate a stereo image with better B/H ratio